An overview of non‐native species invasions in urban river corridors. (7th August 2019) - Francis, Robert A.; Chadwick, Michael A.; Turbelin, Anna J.
Abstract: Recent studies have highlighted cities as prime locations for the introduction, establishment, and spread of non‐native and invasive species. As the hydrological arteries of cities, urban river corridors have an important role to play in influencing species invasions. This overview examines existing literature to consider (a) how the landscape functions of urban river corridors (habitat, conduit, barrier/filter, sink, and source) relate to species invasions; (b) the organismal and geographical foci of research into non‐native species invasions along urban rivers; and (c) the need to more fully consider the roles that non‐native species may play in the recombinant communities of novel urban river ecosystems. The review ends with an identification of research priorities at the intersection of urban river corridor function and invasion biology.